Developing Competency-Based Curriculum Goals - Aisyah Junia Anindya Sari; Nabila Cahya; Maghda Khoirunnisa (The Future of Education Journal, 2025)
This article discusses the importance of developing competency-based curriculum goals in education. A competency-based curriculum is designed to help students acquire practical skills that can be applied in real-life situations and workplaces, alongside their theoretical knowledge. The development of competency-based curriculum goals involves analyzing the needs of industries, society, and the ever-evolving technological advancements. This curriculum emphasizes achieving clear, measurable learning outcomes that are relevant to global demands. Furthermore, this article also explores the steps that educators and educational institutions can take to design and evaluate a competency-based curriculum to enhance the quality of education and prepare students for future challenges.